The Natural History of a Musculoskeletal Clinical Researcher. Issue 1 (21st September 2021) - Zia, Nawal; Evans, Scott; Azzopardi, Christine; James, Steven; Botchu, Rajesh
Background: Clinicians face several barriers to career progression in academia. The natural career progression of acclaimed researchers in musculoskeletal medicine will be analysed to provide a road map for a future researcher. Methods: A retrospective PubMed database search for 32 UK-based researchers in musculoskeletal medicine (orthopaedic surgeons, musculoskeletal radiologists, and rheumatologists) was performed. Researchers with over 10 years in research since their primary medical qualification were included in the study. The number of publications per year were analysed for each researcher. Results: Consultants published a median of 98 papers during their working career and a range of 51 to 399. It took a median of nine years for the first paper to be published (range = 1–27 years). It took a median number of 15 years for a clinician to reach their first peak (range = 6–34). The median number of years spent at the "peak" of one's research career was 2 (range = 1–24). Conclusions: This is the first study to provide a road map for a musculoskeletal clinical researcher. This study identifies a need for structural change to support and encourage clinicians to participate in research. This can be introduced through a range of methods such as mentorship schemes, medical school workshops, and academic training programmes.